Concept Design of Strategic Management for Non – Profit Organization in Slovakia - Eva KICOVA; Olga PONISCIAKOVA (Communications of International Proceedings, 2020)
Society in one country consists of three sectors - private, public and non-profit coexist and influence and complement each other. We include in the private sector all companies and various companies established for the purpose of making a profit. The non-profit sector is usually referred to as the third sector. It represents the part of the company that controls the activities not offered or insufficiently prepares the first two sectors. The tertiary sector has an irreplaceable function in every state. The very functioning of non-profit organizations that operate in the market will be long-term. Only in this way can they fulfil their purpose in society. For this reason, we focused on the strategic management of these companies, in order to create a conceptual proposal for strategic management for non-profit organizations. We used the methods of analysis, synthesis and interrogation for the chosen goal. We consider the most important benefit of the proposed concept of strategic management for non-profit organizations to be a real opportunity to put their strategy into practice and thus support their successful fulfilment of their mission and vision.
Keywords: Management; Strategic Management; Non-Profit Organization.